BMP9 promotes osteogenic differentiation of SMSCs by activating the JNK/Smad2/3 signaling pathway. Issue 4 (3rd November 2019) - Zheng, Weiwei; Chen, Qian; Zhang, Yu; Xia, Rui; Gu, Xueping; Hao, Yuefeng; Yu, Zepeng; Sun, Xingwei; Hu, Dan
Abstract: Synovial mesenchymal stem cells (SMSCs) with high proliferation and multi differentiation ability, and low immunogenicity have attracted research attention for their potential application in tissue engineering. Once their ability of osteogenesis is strengthened, it will be of practical value to apply the SMSCs in the field of bone regeneration. The current study aimed to investigate the osteogenic characteristics of SMSCs induced by bone morphogenetic protein 9 (BMP9) both in vitro and in vivo and to elucidate the mechanism underlying these characteristics. Specifically, different BMPs were assessed to determine the protein that would be the most favorable for stimulating osteogenic differentiation of SMSCs following their separation. The BMP9‐enhanced osteogenesis of SMSCs was fully investigated in vitro and in vivo, and the c‐Jun N‐terminal kinase (JNK)/Smad2/3 signaling pathway stimulated by BMP9 was further explored. Our data suggested that BMP9 could significantly promote gene and protein expression of runt‐related transcription factor 2, alkaline phosphatase, osteopontin, and osteocalcin, and SP600125, a JNK‐specific inhibitor, could effectively decrease this tendency. Similar results were also confirmed in rats with cranial defects. In conclusion, our study indicated that BMP9 promotes bone formation both in vitro and in vivo possibly by activating the JNK/Smad2/3 signaling pathway. Abstract : The current study confirmed the osteogenic characteristics of synovial mesenchymal stem cells induced by bone morphogenetic protein 9 in vitro and vivo and explored the underlying mechanism behind it.